Clinical characterizatión of cutaneous vascular malformations (Boletin Médico de Postgrado, 2024)
A descriptive ambispective cross-sectional study was carried out to determine the clinical characterization of cutaneous vascular malformations (VM) in 82 patients who attended the consultation of the Dermatology Service of the Hospital Central Universitario Dr. Antonio María Pineda of Barquisimeto, Lara state, Venezuela. The majority of cases were of the female gender and the average age was 3,2 ± 1,65 years of age. Lesions were located more frequently on face, anterior thorax and scalp. Up to four lesions were identified with size modification according to the number of lesions (2.8 ± 1.7cm and 3.4 ± 1.18 cm). Color changed between violaceous, erythematous and erythematous-violaceous. Consistency was soft and temperature oscillated from normothermic to hyperthermic.